Development of methods for risk-oriented analytical assessment of financial performance of wine-producing enterprises - Marchuk, Uliana; Gutsalenko, Liubov; Bondar, Mykola; Gumenna-Derii, Mariia; Tsaruk, Nataliia (Technology audit and production reserves, 2026)
The object of research is the process of forming a comprehensive risk-oriented system for analyzing the financial performance of wine-producing enterprises. The development of this methodology will ensure systematic identification, quantitative assessment and integration of risks at all stages of the value chain. Existing approaches limit the ability to form a risk profile for operations and justify effective management decisions in conditions of instability. Traditional methods of analytical assessment do not allow for the multidimensionality of risk factors and the complex nature of their impact on changes in efficiency to be reflected. The use of an integrated risk criterion ensures more accurate forecasting of financial performance trends, increasing the effectiveness of the management control system. The developed methodology for assessing the financial performance risk of viticulture and winemaking enterprises based on normalized indicators and integral criteria made it possible to outline the risk dynamics and key parameters of uncertainty. The assessment was carried out in terms of grape varieties and enterprises on a five-level scale, with 2019 identified as the most critical year. The highest risk is in Cabernet 2024 and Rkatsiteli 2024: Alibernet 2024 has the lowest risk; Merlot 2024 has an average risk. The integrated assessment of average risk forms a unified information model that supports strategic decisions and enhances competitiveness. The applied nature of the study is determined by its focus on supporting management decisions in the financial and economic management of grape and wine-producing enterprises. The integrated risk assessment methodology ensures the identification and quantitative measurement of risks at all stages of the value chain, which allows identifying critical factors of financial performance and justifying the optimization of production and cost parameters.